Application of Non-Linear Extrapolations for the Convergence Acceleration of Source Iteration. Issue 5 (28th July 2016) - Picca, Paolo; Furfaro, Roberto; Ganapol, Barry D.
ABSTRACT: Our paper presents a comparison of the extrapolated-based acceleration of source iteration (SI) techniques against classical acceleration schemes. The basis of the SI method is reviewed before presenting its combination with non-linear extrapolations. Two acceleration strategies are discussed, one based on the extrapolation of the source term for the SIs and the other based on the acceleration of the solution itself. Their performances are compared with classical acceleration techniques (diffusion synthetic acceleration and transport synthetic acceleration, showing the effectiveness of the combination of extrapolation with standard acceleration schemes.